A rapid and efficient approach for Neurospora crassa transformation using low melting point agarose purified DNA. - Q. Liu; J. C. Dunlap (Fungal Genetics Reports, 1988)
A rapid and efficient approach for Neurospora crassa transformation using low melting point agarose purified DNA.